2016
DOI: 10.1177/0022034516645332
|View full text |Cite
|
Sign up to set email alerts
|

SOCS-3 Regulates Alveolar Bone Loss in Experimental Periodontitis

Abstract: The host immune response plays a key role in bacteria-induced alveolar bone resorption. Endogenous control of the magnitude and duration of inflammatory signaling is considered an important determinant of the extent of periodontal pathology. Suppressor of cytokine signaling (SOCS) proteins are inhibitors of cytokine signaling pathways and may play a role in restraining periodontal inflammation. We hypothesized that SOCS-3 regulates alveolar bone loss in experimental periodontitis. Periodontal bone loss was ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 29 publications
3
31
0
Order By: Relevance
“…18,19 Furthermore, a recent report identified SOCS3 as a critical negative regulator of alveolar bone loss in experimental periodontitis induced in SOCS-3-knockout mice. 20 Supporting these findings, our group recently reported that SOCS1 and SOCS3 expression is correlated with the overall severity of inflammation and the expression of proinflammatory cytokines in a rat model of ligature-induced periodontitis. 21 This model is marked by the presence of a plethora of bacterial virulence factors from endogenous bacterial species resulting in periodontal inflammation and bone loss.…”
Section: Introductionmentioning
confidence: 63%
“…18,19 Furthermore, a recent report identified SOCS3 as a critical negative regulator of alveolar bone loss in experimental periodontitis induced in SOCS-3-knockout mice. 20 Supporting these findings, our group recently reported that SOCS1 and SOCS3 expression is correlated with the overall severity of inflammation and the expression of proinflammatory cytokines in a rat model of ligature-induced periodontitis. 21 This model is marked by the presence of a plethora of bacterial virulence factors from endogenous bacterial species resulting in periodontal inflammation and bone loss.…”
Section: Introductionmentioning
confidence: 63%
“…Mice with a null-mutation of Socs-3 , the “Suppressor of Cytokine Signaling” (SOCS)-3 proteins, develop periodontitis when they are infected with P. gingivalis . In this specific experimental periodontitis mouse model, the investigators have noted increased expression of RANKL and an increase in osteoclast activity ( 39 ); moreover, in line with the function of Socs-3 , they showed an increased expression of pro-inflammatory cytokines such as IL-1β and IL-6.…”
Section: Mouse Models Of Genes Associated With the Inflammatory Respomentioning
confidence: 88%
“…Apparently, analogous to Bert Vogelstein’s famous second hit hypothesis for developing colorectal cancer ( 97 ), where two hits are required to develop disease (colorectal cancer), one could thus postulate that both an underlying genetic defect and a bacterial challenge are required for developing periodontitis. For seven genes: IL17-ra ( 10 ), IL1-ra ( 50 ), Socs-3 ( 39 ), IL-10 as well as its downstream modulator Stat3 ( 55 ) and adhesion molecules Icam-1 ( 11 ) and Beta6 integrin ( 27 ), only the combination of functional loss with bacterial pressure resulted in periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the percentage of alveolar bone loss was calculated using the formula: alveolar bone loss = 1‐(remaining bone volume/VOI) × 100, using an analysis software and considering the VOI as 100%. For SEM analysis, bone loss was quantified at magnification ×30 using a scanning electron microscope, determining the area of bone loss between the mesial surface of M/M1 and the distal surface of D/M3, and between the CEJ and the alveolar bone crest (ABC), as described previously . All data were collected by a single observer (GM) who was masked to conditions of the maxillae samples.…”
Section: Methodsmentioning
confidence: 99%